Editorial - Heitmeyer, Wilhelm; Massey, Douglas S.; Messner, Steven F.; Sidanius, James; Wieviorka, Michel (International Journal of Conflict and Violence (IJCV), 2007)
The 2nd issue of the International Journal of Conflict and Violence focuses on the subject of terrorism. Terrorism has long been a worrisome phenomenon with serious impacts on and implications for the affected societies. Now, since 9/11, fighting international terrorism has moved to the very top of the agenda of the international community, or at least its western members. The special ICJV issue is intended to foster a deeper understanding of this critically important topic.